Perancangan Sistem Kunci Pintu Rumah Dengan Sensor Fingerprint Berbasis Arduino - Muhamad Taufik; Munawaroh (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Digital smart doorlocks and home automation still have weaknesses in the mobile app system, where users only need one button to open the door wirelessly which is considered too dangerous, if the user's smartphone is stolen, home security will also be threatened. The method used in the development of the smart doorlock system is a data collection method in the form of observation and literature studies, the data collection process is taken directly during the tool implementation process. The design of the mobile door lock system application uses a codular application while the door lock device uses an Arduino Uno board, fingerprint sensor and keypad. Fingerprint and PIN sensors are used as additional security for both smartphones and Arduino, to connect the device to a smartphone using the hc-05 Bluetooth module. This tool is also equipped with an LCD as a menu viewer that is accessed. The results of this research are that the Smart Dorlock application security system that is built already has additional security to open the door, namely in the form of a fingerprint sensor and PIN instead of a button to open the door, the application also has additional features in the form of App Lock to lock applications.